Catullus and the poetics of Roman manhood - Wray, David, 1959- (Cambridge University Press, 2001)
"This book applies comparative cultural and literary models to a reading of Catullus's poems as social performances of a "poetics of manhood": a competitively, often outrageously, self-allusive bid for recognition and admiration. Earlier readings of Catullus, based on Romantic and Modernist notions of "lyric" poetry, have tended to focus on the relationship with Lesbia and to ignore the majority of the shorter poems, which are instead directed at other men. Professor Wray approaches these poems in the light of new models for understanding male social interaction in the pre-modern Mediterranean, placing them in their specifically Roman historical context while bringing out their strikingly "postmodern" qualities